Locality Competent Flash Translation Layer (LC-FTL) for NAND Flash Memory - Islam, A.B.M Rezbaul (The Graduate School, Ajou University, 2012)
Flash memory based memory devices are getting more and more admired. It has many advantages compared with traditional hard disk drives. It is well established fact that, random access pattern of different workload influences on the performance of flash memory. However, design of Flash Translation Layer (FTL) which performs logical to physical address translation, should be changed into a new paradigm. Present trend on FTL design is locality based FTL. In this thesis. a FTL, called Locality Competent FTL or LC-FTL is proposed, where both type of locality- temporal locality and spatial locality are considered.LC-FTL divides file system requests in two kinds- single page and multiple page request according to size, for using locality properly. To utilize both of locality some small active mappings are temporally stored in SRAM . However, total three small tables and a buffer is maintained in cache. Buffer is used to divide requests, whereas two tables store active mappings. Existing FTL involve a lot of overhead accesses because of uncached data.LC-FTL use maximum benefit from aforementioned localities to improve performance. Proposed FTL is based on page level mapping scheme. The experimental result shows that, proposed FTL outperforms less read, write and most importantly erase operation than other existing FTLs.
학위논문(석사)아주대학교 일반대학원 :컴퓨터공학과,2012. 2